2015
DOI: 10.1139/cjfas-2014-0528
|View full text |Cite
|
Sign up to set email alerts
|

Chinook salmon outmigration survival in wet and dry years in California’s Sacramento River

Abstract: Outmigration survival of acoustic-tagged, hatchery-origin, late-fall-run Chinook salmon (Oncorhynchus tshawytscha) smolts from the Sacramento River was estimated for 5 years (2007–2011) using a receiver array spanning the entire outmigration corridor, from the upper river, through the estuary, and into the coastal ocean. The first 4 years of releases occurred during below-average river flows, while the fifth year (2011) occurred during above-average flows. In 2011, overall outmigration survival was two to five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 40 publications
(51 reference statements)
6
85
1
Order By: Relevance
“…This pattern of higher mortality in the downstream versus upstream Delta reaches was also observed for late‐fall‐run Chinook Salmon from the Sacramento River in 2011 (Michel et al. ) and suggests spatial variability in mortality factors within the Delta. This possibility is supported by the observation that the majority of tagged FR Chinook Salmon from the San Joaquin River detected at Chipps Island when all routes were available (i.e., no rock barrier at the head of Old River) came through salvage at the CVP rather than migrating entirely through Delta waters; this is because salvaged fish avoid the downstream reaches of the Delta.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This pattern of higher mortality in the downstream versus upstream Delta reaches was also observed for late‐fall‐run Chinook Salmon from the Sacramento River in 2011 (Michel et al. ) and suggests spatial variability in mortality factors within the Delta. This possibility is supported by the observation that the majority of tagged FR Chinook Salmon from the San Joaquin River detected at Chipps Island when all routes were available (i.e., no rock barrier at the head of Old River) came through salvage at the CVP rather than migrating entirely through Delta waters; this is because salvaged fish avoid the downstream reaches of the Delta.…”
Section: Discussionsupporting
confidence: 57%
“…Additionally, survival through the bays can be lower than survival through the Delta itself for late‐fall‐run Chinook Salmon (Michel et al. ), and Lindley et al. () concluded that ocean conditions contributed heavily to the fall‐run salmon fishery collapse in 2007 and 2008.…”
Section: Discussionmentioning
confidence: 99%
“…In comparing this removal effort with ours, we note that their removals occur in a watershed with much higher baseline survival (Michel et al. ) and better water quality, with effective and sustained removal strategies (a bounty program lasts the entire smolt out‐migration season and has been renewed annually for many years), with lethal take of fish that are not popular to fisherman (i.e., no relocation or public relations issues), and with little evidence of compensatory effects (Beamesderfer et al. ).…”
Section: Discussionmentioning
confidence: 73%
“…Yet, evidence suggests that longer Delta residence times lead to higher mortality rates in salmon smolts (Perry et al 2010;Michel et al 2015). It is conceivable that Delta rearing for SRWRC is an important and successful strategy because they historically used these habitats, and they enter the habitat under cooler winter temperatures when predator metabolism is lower (Yoshiyama et al 1998).…”
Section: Issue 3: Is the Delta An Important Contributor To Srwrc Adulmentioning
confidence: 99%
“…Results of acoustic tagging studies in the Sacramento and San Joaquin rivers have generated important insights into overall low survival, effects of flows and turbidity on survival, diversity in migration behaviors among races of Chinook Salmon, and variability in survival rates among different regions of the river, Delta, and bays (Buchanan et al 2013;Singer et al 2013;Cavallo et al 2015;Michel et al 2015;reviewed in Perry et al 2016). However, most of these studies were conducted on hatcheryorigin salmon from different runs, highlighting the need to expand this approach to gathering comparable information on salmon originating and migrating from Central Valley rivers.…”
Section: Introductionmentioning
confidence: 99%